A new tool for an explantation strategy of HeartMate 3™ left ventricular assist device - Ricklefs, Marcel; Deodhar, Chinmay; Chatterjee, Anamika; Feldmann, Christina; Hanke, Jasmin S.; Heimeshoff, Jan; Merz, Constanze; Deniz, Ezin; Dogan, Guenes; Haverich, Axel; Schmitto, Jan D. (Journal of Thoracic Disease, 2018)
Background: Although rare, recovery of cardiac function after mechanical support of the left ventricle is the most desirable therapeutic goal in the treatment of end-stage heart failure. Methods: Herein, we present a novel implantable device for explantation of the HeartMate 3TM left ventricular assist device (LVAD) in patients, following cardiac recovery, avoiding (re-) sternotomy. Results: This article demonstrates the feasibility of applying this novel device, which fits into the sewing ring of the LVAD. Conclusions: This custom-made mechanical plug offers a promising alternative to standard device-explantation procedures.